Inscriptions of the Aulikaras and their associates - Balogh, Dániel (Beyond boundaries, 2019)
Frontmatter -- Preface -- Acknowledgments -- Contents -- List of Figures -- A Concordance of Inscription Titles -- Legend for Editions and Translations -- List of Abbreviations -- Preliminaries -- Editorial Conventions -- Dates and Dating -- Palaeography -- Part I: Context -- Introduction: The Aulikara Power Network -- The Origin of the Aulikaras -- The Aulikaras and Their Associates -- Part II: Inscriptions -- A. Major Inscriptions -- B. Minor Inscriptions -- C. Unpublished Inscriptions -- Appendix 1. Prosopography -- Appendix 2. Gazetteer -- Bibliography -- Index